Francisella tularensis Outer Membrane Vesicles Participate in the Early Phase of Interaction With Macrophages - Pavkova, Ivona; Klimentova, Jana; Bavlovic, Jan; Horcickova, Lenka; Kubelkova, Klara; Vlcak, Erik; Raabova, Helena; Filimonenko, Vlada; Ballek, Ondrej; Stulik, Jiri (Frontiers in Microbiology, 2021)
Francisella tularensis is known to release unusually shaped tubular outer membrane vesicles (OMV) containing a number of previously identified virulence factors and immunomodulatory proteins. In this study, we present that OMV isolated from the F. tularensis subsp. holarctica strain FSC200 enter readily into primary bone marrow-derived macrophages (BMDM) and seem to reside in structures resembling late endosomes in the later intervals. The isolated OMV enter BMDM generally via macropinocytosis and clathrin-dependent endocytosis, with a minor role played by lipid raft-dependent endocytosis. OMVs proved to be non-toxic and had no negative impact on the viability of BMDM. Unlike the parent bacterium itself, isolated OMV induced massive and dose-dependent proinflammatory responses in BMDM. Using transmission electron microscopy, we also evaluated OMV release from the bacterial surface during several stages of the interaction of Francisella with BMDM. During adherence and the early phase of the uptake of bacteria, we observed numerous tubular OMV-like protrusions bulging from the bacteria in close proximity to the macrophage plasma membrane. This suggests a possible role of OMV in the entry of bacteria into host cells. On the contrary, the OMV release from the bacterial surface during its cytosolic phase was negligible. We propose that OMV play some role in the extracellular phase of the interaction of Francisella with the host and that they are involved in the entry mechanism of the bacteria into macrophages.